STRATEGY TO IMPROVE SPORTS TOURISM IN THE JAKABARING SPORT CITY AREA, PALEMBANG CITY - Putri Alwahdaniyah Wahyuni (International Journal of Sustainable Competitiveness on Tourism, 2023)
Jakabaring Sport City (JSC) in Palembang, South Sumatera Province has become the largest centralized sport complex in Asia. This sport complex is the host of PON XVI 2004, SEA GAMES XXVI 2011 and ASIAN GAMES XVIII 2018. With the presence of several mega events, the Jakabaring Sport City (JSC) is one of the centres of international standard sport and tourism activities in Indonesia. Based on the data from Dinas Pemuda dan Olahraga, Palembang City, the number of international sporting events held in Jakabaring Sport City (JSC) has increased from 2015 by 14 events until 2019 increase to 3 events. From the existence of this matter, this research aims to study the actual development and potential in the tourism sector. The method used in this research is descriptive method by obtaining qualitative. And data collection techniques using literature studies. The data that has been obtained is than analyzed using an interactive analysis method by wich researchers are required to conduct data collection activities, data reduction, data presentation, and finally conclusions are obtained. This research resulted in an assessment direction on strategies to increase sport activities especially to increase the sport tourism events in Jakabaring Sport City (JSC), Palembang city